Mangrove community structure on Kapo-Kapo Island, Mandeh Region, Pesisir Selatan Regency - Kamal, Eni; Yuspardianto, Yuspardianto; Bukhari, Bukhari; Pratama, Ananda (Universitas Malikussaleh, 2023)
This study aimed to analyze the structure of the mangrove community including the identification of species, density, frequency, dominance, important value index, and mangrove basal area on Kapo-Kapo Island, Mandeh Region, Pesisir Selatan Regency. Mangrove community structure data collection was carried out by direct observation, starting with data collection and identification of species, number of individuals and diameter of mangrove tree. In collecting data on the structure of the mangrove community, water quality measurements were also carried out pH, salinity, temperature and looking at the substrate of the mangrove. Based on the results of the study, identified species of mangrove in Kapo-Kapo Island, Mandeh Region, Pesisir Selatan Regency, namely R. apiculata, S. casseolaris, and L. littorea. The average values of KR, FR, DR and INP on tree-level mangroves at R. apiculata were 97.00%, 65.00%, 93.02%, and 255.03%. S. casseolaris 1.82%, 28.33%, 6.14%, and 36.29%. L. littorea 1.18%, 6.67%, 0.84%, and 8.68%. The species R. apiculata had the highest Important Value Index from the tree level of the most dominating species on each transect.Keywords: Kapo-Kapo Island; mangrove; structure of the mangrove community